Weather Station Based Rasberry Pi - Adrian Valendra Nekwek; Jhon Kristel Sabathino Pigome; Nurul Firdaus (Asosiasi Riset Teknik Elektro dan Informatika Indonesia, 2024)
Research on weather elements is very necessary for the benefit and welfare of mankind, the observed weather elements will become material for predicting the weather in the future. This data is also used to prevent the risk of adverse impacts caused by the weather itself. To measure the weather with this automatic system, a tool called AWS is needed. The AWS design requires a Rasberry Pi. By using this Rasberry Pi we can monitor weather changes originating from BMKG via the web in the form of an Analog Gauge.